THE EFFECTIVENESS OF ONLINE LEARNING FOR ISLAMIC-BASED HIGHER EDUCATION TOWARDS A NEW NORMAL ERA IN KOTA MEDAN - Dedi Amrizal; Yusriati Yusriati (Proceeding International Seminar of Islamic Studies, 2021)
The implementation of online learning is applied throughout all Islamic-based universities in Kota Medan. Problems arise among lecturers and students when learning takes place. The implementation of online learning at the beginning of the pandemic was challenging and fun, but after a few months it turned out to give excess to lecturers, students and the learning process. This study aims to (1) determine the implementation of online learning carried out by Islamic-based university lecturers; (2) knowing the implementation of online learning experienced by Islamic-based university students; (3) to analyze the constraints in implementing the online learning process for Islamic-based higher education institutions in Kota Medan. This study uses a descriptive research method with a survey approach to prove that the implementation of online learning in Medan has been implemented optimally. Furthermore, through this method it will also be seen the impact of this online learning continuously for one semester for lecturers and students. The results showed that there had been a decrease in the quality of work among lecturers and a decrease in enthusiasm for learning among students. In addition, there is also a high level of boredom among students caused by the lifeless atmosphere of the lecture. Finally, the most dominant thing is that this online learning method is felt by students and lecturers as burdensome and expensive.Keywords: Online Learning, Higher Education, New Normal Era